Analisis Praktik Pedagogis Guru dalam Menghadapi Variasi dan Degradasi Karakter Peserta Didik Sekolah Dasar dalam Tantangan Pendidikan Abad Ke-21 - Dela Puspita; Intan Putri Kamilah; Rifqa Gusmida Syahrun Barokah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze teachers’ pedagogical practices in addressing the variation and degradation of elementary school students’ character within the challenges of 21st-century education. The research employed a qualitative approach with a descriptive design to obtain an in-depth understanding of classroom phenomena. Data were collected through semi-structured interviews with teachers from grades I to VI and classroom observations conducted naturally without informing students, ensuring authentic behavioral data. The study used 18 character values as indicators to examine students’ character development. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured using source and technique triangulation. The findings reveal that each grade level demonstrates different patterns of character variation and degradation. Positive character traits such as independence, communication skills, and curiosity tend to develop progressively, while issues such as discipline, responsibility, perseverance, and reading interest show signs of decline. Teachers respond to these conditions through adaptive pedagogical practices, including habituation, role modeling, collaborative learning, and project-based activities. These findings indicate that effective pedagogical practices play a crucial role in shaping students’ character and must be aligned with students’ developmental stages. The study implies that adaptive, contextual, and value-oriented teaching strategies are essential to support character development and meet the demands of 21st-century education.